2017
DOI: 10.3847/2041-8213/aa8861
|View full text |Cite
|
Sign up to set email alerts
|

Circumgalactic Oxygen Absorption and Feedback

Abstract: OVI absorption in quasar spectra caused by intervening circumgalactic atmospheres suggests a downturn in the atmospheric column density in sightlines passing beyond about 100 kpc from central star-forming galaxies. This turnover supports the hypothesis that the oxygen originates in the central galaxies. When converted into oxygen space density using an Abel integral inversion, the OVI columns require > ∼ 10 9 M of oxygen concentrated near 100 kpc. Circumgalactic gas within this radius cools in less than 1 Gyr … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 30 publications
4
43
1
Order By: Relevance
“…Alternative versions of the halo gas profile have also been derived in the context of feedback which modifies the distribution away from the NFW profile by altering the entropy distribution of the gas. Mathews & Prochaska (2017) introduced such a model to investigate the observed profile of N OVI absorption in present-day L * galaxies. We generalize their modified NFW (mNFW) model as,…”
Section: Halo Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative versions of the halo gas profile have also been derived in the context of feedback which modifies the distribution away from the NFW profile by altering the entropy distribution of the gas. Mathews & Prochaska (2017) introduced such a model to investigate the observed profile of N OVI absorption in present-day L * galaxies. We generalize their modified NFW (mNFW) model as,…”
Section: Halo Modelsmentioning
confidence: 99%
“…High column density measurements of O +5 have revealed a more highly-ionized plasma, interpreted by many as a tracer of the predicted T 10 6 K virialized halo gas (e.g. Oppenheimer et al 2016;Faerman et al 2017;Mathews & Prochaska 2017). Estimating the mass of this putative, hot-phase is even more challenging because it is difficult to assess the degree of H i absorption associated with it and one rarely has access to neighboring ions of the same element to constrain the ionization state of the gas.…”
Section: Introductionmentioning
confidence: 99%
“…29) while f O vi which depends mainly on T is roughly independent of M. Hence, in principle a cooling flow with M ∼ 25 SFR could reproduce the O vi observations, though such a model would have t cool < t ff and hence would be unstable. It has been shown that any model which assumes O vi traces radiatively cooling gas requires M SFR (Mathews & Prochaska 2017;Faerman et al 2017;McQuinn & Werk 2018;Stern et al 2018).…”
Section: Ovi Absorptionmentioning
confidence: 99%
“…Since the hydrostatic equation on its own is insufficient to fully specify the structure of the halo gas, these studies evoked additional assumptions on the density or entropy profile. Specifically, Maller & Bullock (2004) assumed a flat entropy profile out to R cool , Faerman et al (2017) derived the density profile from the average X-ray emission and absorption in the MW and from the O vi absorption around external galaxies, Mathews & Prochaska (2017) assumed a density which follows the dark matter density with a flat entropy core, and Voit (2018) assumed an entropy profile which yields t cool /t ff ≈ 10 at all radii. In the cooling flow solutions for the MW halo gas , the pressure profile is also close to hydrostatic, since the correction to the momentum equation is of order M 2 , while M is small at halo radii (≈ 0.1 at 100 kpc, eqn.…”
Section: Comparison With Hydrostatic Modelsmentioning
confidence: 99%
See 1 more Smart Citation